A Nationwide Analysis of Geriatric Odontoid Fracture Incidence, Complications, Mortality, and Cost. Issue 2 (15th January 2021) - Alluri, Ram; Bouz, Gabriel; Solaru, Samantha; Kang, Hyunwoo; Wang, Jeffrey; Hah, Raymond J.
Abstract : Study Design: Retrospective database analysis. Objective: To identify nationwide temporal trends in management of geriatric odontoid fractures and to compare comorbidities, inpatient complications, hospital characteristics, and cost between patients receiving operative versus nonoperative management. Summary of Background Data: The treatment of geriatric odontoid fractures remains controversial with some studies demonstrating decreased mortality and improved functional outcomes associated with operative management and significant morbidity associated with halo devices during nonoperative management. Methods: Patients between ages 65 to 90 years with odontoid fractures who underwent operative or nonoperative management between the years 2003 and 2017 were identified in the National Inpatient Sample (NIS) database. Year of injury, demographic variables, comorbidities, inpatient complications, mortality, length of stay, inpatient cost, and hospital characteristics were compared between operative and nonoperative treatment groups. Results: Thirty two thousand four hundred nineteen patients (average age 77 yr, 54% female) were included in the final analysis. Operative treatment occurred in 21, 954 (67%) patients and nonoperative treatment occurred in 10, 465 (32%). In 2003, operative treatment occurred in 46% of patients and nearly doubled to 86% in 2017, with an average increase of 3.7% per year ( P  < 0.001). Patients undergoing operative management had a lower prevalence of at least one major medical comorbidity (76% vs. 83%, P  < 0.001). Patients undergoing operative treatment demonstrated higher odds of developing most complications, particularly pulmonary, gastrointestinal, and renal ( P  < 0.01). Inpatient mortality was 3.6% in patients receiving operative treatment and 5.9% in patients receiving nonoperative treatment ( P  < 0.001). Average cost per episode of care during the study period was $131, 855 for operative treatment and $65, 374 for nonoperative treatment ( P  < 0.001). Conclusion: This study demonstrates a clear national paradigm shift in the management of geriatric odontoid fractures, wherein operative management nearly doubled from 46% in 2003 to 86% in 2017. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textPatients between ages 65 and 90 with odontoid fractures who underwent operative or nonoperative management were identified. The incidence of operative treatment nearly doubled to 86% by 2017. Operative treatment had higher inpatient complications, lower mortality, and more than twice the inpatient cost of care.